Comparison of retinal and choroidal vascular changes via optical coherence tomography angiography between pseudoexfoliative glaucoma and pseudoexfoliation syndrome and control group - Mohammad Hossein Ahoor; Rana Sorkhabi; Farhad Najafzadeh; Sheyda Mahmoudzadeh; Amin Arasteh; Tahereh Attar Gharamaleki (Photodiagnosis and Photodynamic Therapy)
Background: This study aims to evaluate the differences in retinal and choroidal vasculature using optical coherence tomography angiography (OCTA) in patients with pseudoexfoliative glaucoma (PEX-G) and patients with pseudoexfoliation syndrome without glaucoma (PEX-S) and the control group. Materials and Methods: In this cross-sectional study, 25 patients with PEX-G, 27 PEX-S cases, and 25 patients as the control group (C) were evaluated. All patients and the control group underwent macular and optic nerve head (ONH) OCTA, performed using the Optovue device. The foveal and parafoveal vascular density (VD) in superficial capillary plexus (SCP) and deep capillary plexus (DCP), foveal avascular zone (FAZ) area, outer retina flow area, choriocapillaris flow area, peripapillary VD, and retinal nerve fiber layer (RNFL) thickness in the macula and peripapillary region were assessed. Results: 77 eyes of 77 patients were included. The mean foveal SCP VD in the control group was 9.62 % and 8.92 % higher than in the PEX-S and PEX-G groups; the median foveal DCP VD had 11.3 % and 13.2 % higher values in the controls. The PEX-S and PEX-G groups showed no differences regarding the macular microvasculature. The intradisc VD and the peripapillary VD were 7.5 % and 17.9 % lower in the PEX-G group compared to the controls. Besides, the peripapillary VD was significantly correlated with the RNFL thickness (R2:0.789, p:<0.0001). Conclusion: In patients with PEX, regardless of glaucoma, the retinal VD showed deficiencies compared to the controls. Also, the peripapillary VD was strongly correlated with the RNFL thickness. These findings mean that retinal vascular changes might precede the development of glaucoma in PEX syndrome and can even be its cause.